Нормативи навантаження на лікарів стаціонарних відділень офтальмологічного профілю лікарень інтенсивного лікування, виходячи з обсягів виконуваної роботи - V. H. Ginzburh; V. M. Lekhan; O. Ye. Lamza (Medičnì Perspektivi, 2013)
The research was done with the application of “Methodology of definition of normative workload of physicians of in-hospital departments of intensive care hospitals” approved by the Ministry of health care of Ukraine on the basis of two ophthalmological departments of hospital N 8 in Dniptropetrovsk, where a routine and urgent intensive and secondary care of ophthalmological profile is provided in twenty-four-hour regime.Normative workload of ophthalmologists is substantiated coming from on the number of cured patients and number of surgeries per year.